RSSI-WIFI BASED INDOOR POSITION TRACKING SYSTEM USING SUPPORT VECTOR MACHINE - Ferdian Agung Sudrajat, Irsan
One of the services that are widely used on smartphones caused by the rapid development of technology is position tracking. Position tracking can be used to track objects or people. Such as tracking in logistics warehouses, patients in hospitals or people at the airport. A popular method for positioning is the Global Positioning System (GPS). However, when indoors, GPS has limitations because the signal is degraded by building structures. Therefore, an indoor position tracking system is needed to provide a more precise position estimate. This indoor position tracking system utilizes the Received Signal Strength Indicator (RSSI) from the WiFi router. A WiFi router is used because it has the advantage that the device has been installed in many places. Received Signal Strength Indicator (RSSI) is the amount of radio signal power received from the transmitter. The research area is divided into 49 points and 10 routers are used. The RSSI value of each point is stored as the identity (fingerprint) of each point. The stored RSSI value will be compared with the RSSI obtained by the user in real-time to determine the user's position. Then, an alert system is created using the Support Vector Machine (SVM) to find out if there are any clumsiness in the user's position. The accuracy of the support vector machine is 100%. The results of positioning and system alerts will be displayed on the web page.